The Nucleoskeleton: Crossroad of Mechanotransduction in Skeletal Muscle - Iyer, Shama R.; Folker, Eric S.; Lovering, Richard M. (Frontiers in Physiology, 2021)
Intermediate filaments (IFs) are a primary structural component of the cytoskeleton extending throughout the muscle cell (myofiber). Mechanotransduction, the process by which mechanical force is translated into a biochemical signal to activate downstream cellular responses, is crucial to myofiber function. Mechanical forces also act on the nuclear cytoskeleton, which is integrated with the myofiber cytoskeleton by the LINC (linker of the nucleoskeleton and cytoskeleton) complexes. Thus, the nucleus serves as the endpoint for the transmission of force through the cell. The nuclear lamina, a dense meshwork of lamin IFs between the nuclear envelope and underlying chromatin, plays a crucial role in responding to mechanical input; myofibers constantly respond to mechanical perturbation via signaling pathways by activation of specific genes. The nucleus is the largest organelle in cells and a master regulator of cell homeostasis, thus an understanding of how it responds to its mechanical environment is of great interest. The importance of the cell nucleus is magnified in skeletal muscle cells due to their syncytial nature and the extreme mechanical environment that muscle contraction creates. In this review, we summarize the bidirectional link between the organization of the nucleoskeleton and the contractile features of skeletal muscle as they relate to muscle function.